Nutritional therapy in malnourished young adolescent: from epileptic state to catch up growth - Andi Faradilah; Rima January; Suryani As'ad; Syatirah Jalaluddin (Universitas Islam Negeri Alauddin Makassar, 2022)
Epilepsy and malnutrition in children are a vicious circle. Epilepsy with non-treated recurrent seizures could lead to malnutrition. Conversely, malnutrition which results in macronutrient and micronutrient deficiencies also potential to trigger seizures. We reported an adolescent, male, 14 years 6 months, with epileptic state accompanied by malnutrition status. In this case, a repeated seizures cause the unconscious level of patient and at risk of respiratory failure. Multidisciplinary therapy was arranged by anesthesiologist, pediatrician, and clinical nutritionist. The treatments began with procedure of a ventilator installation, anticonvulsant drugs, and administration of a nasogastric tube for accessing nutrition intake. Nutrition therapy focused on managing diet in critical ill children and attention to undernourished conditions that require long-term treatment. The target of nutrition calorie was achieved on day 6-8 of treatment through enteral to oral diet. Finally, nutrition education for catch-up growth was given to the families to be applied during the recovery and rehabilitation period at home.